The effect of Borag officinalis infusion in histological structure of lung and some blood parametars in white male mice - Kawkab S.Al-qaissi; Mousa J.Al-Humesh; Sarah F. Al-shamani (Tikrit Journal of Pure Science, 2023)
This study is designed to recognize the side effects of Borago officinalis infusion on the histological structure of  lung and some blood  parameters (WBCs, PLTs, Hb ,P.C.V ).